A biomimetic model composed of injectable 3D muscle-like tissue, stromal and immune cells for recapitulating the rapid immune signature predictive of mRNA vaccine immunogenicity - Etna, Marilena Paola; Fuoco, Claudia; Severa, Martina; Ricci, Daniela; Sinigaglia, Alessandro; Lucca, Camilla; Cairo, Giada; Bottazzi, Barbara; Garlanda, Cecilia; Palamara, Anna Teresa; Barzon, Luisa; Gargioli, Cesare; et al. (Frontiers in Immunology, 2025)
BackgroundSystem vaccinology identified an early innate signature associated with vaccine-mediated protection whose induction is likely to involve both immune and non-immune cells.MethodsTo dissect muscle and stromal cell contribution, we simulated in vitro anti-COVID19 BNT162b2 mRNA vaccine intramuscular administration in human primary cell systems composed of 3D muscle-like tissue (3D-MT), fibroblasts, and peripheral blood mononuclear cells (PBMC).ResultsBNT162b2 vaccine was recognized by all cell types, although fibroblasts only translated the spike antigen. Factors from vaccine-injected 3D-MT stimulated monocyte and macrophage recruitment and promoted inflammatory macrophage activation, while stromal factors improved dendritic cell frequency and activation. Conditioned media from vaccine-exposed 3D-MT and fibroblasts elicited in PBMC the expression of an early innate immune module previously associated with protective responses in BNT162b2 vaccinees.ConclusionThus, models combining human PBMC, stromal and muscle cells could be employed for the in vitro validation of system vaccinology findings and non-animal vaccine pre-clinical testing.